2008
DOI: 10.1111/j.1365-2249.2008.03649.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate and severe malnutrition in rats on splenic T lymphocyte subsets and activation assessed by flow cytometry

Abstract: SummaryMalnutrition is distributed widely throughout the world and is a particular problem in developing countries. Laboratory animals have been very useful in studying the effects of varying levels of malnutrition because non-nutritional factors that affect humans may be controlled. The objective of the present study was to determine the effects of moderate and severe malnutrition on lymphocyte proportions and activation markers of T cells in experimentally malnourished rats during lactation by flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
5
24
0
Order By: Relevance
“…In the present study, our data demonstrate that perinatal undernutrition induced changes in the morphometry of the splenic lymphoid follicles in endotoxemic rats. Our findings are in agreement with a previous study which reported that the spleen of adult rats is susceptible to undernutrition in early life [7] . In fact, the critical period of development of the spleen begins during gestation and the spleen acquires its characteristic shape early in the fetal period [7] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present study, our data demonstrate that perinatal undernutrition induced changes in the morphometry of the splenic lymphoid follicles in endotoxemic rats. Our findings are in agreement with a previous study which reported that the spleen of adult rats is susceptible to undernutrition in early life [7] . In fact, the critical period of development of the spleen begins during gestation and the spleen acquires its characteristic shape early in the fetal period [7] .…”
Section: Discussionsupporting
confidence: 83%
“…In animals, neonatal undernourishment (multideficient diet with 7% of protein) induced a decrease in in vitro nitric oxide release by alveolar macrophages of adult rats when compared with controls whose mothers had been fed a normal diet (23% of protein) [6] . Malnourished rats (litters with 16 pups), show reductions in the absolute and relative numbers of splenic lymphocyte subpopulations [7] . In fact, changes in immune cell dynamics are often observed when the organism is challenged by either infectious stressors, such as endotoxins or exotoxins of pathogens, or noninfectious stressors that activate the hypothalamic-pituitary-adrenal (HPA) axis [8] .…”
mentioning
confidence: 99%
“…The immediate consequence of this atrophy is leucopenia, decreased CD4/CD8 ratio and increased number of immature T cells in the periphery. Recently, Cortés-Barberena et al (36) observed that significant lower numbers of CD3+ lymphocytes were present in the spleen of moderately and severely malnourished rats. They also detected a considerable impairment of T cell activation characterized by decreased expression of CD25 and CD71 in these cells.…”
Section: Malnutrition Affects Immunitymentioning
confidence: 99%
“…DOI 10.1002/em because the prevalence of these degrees of malnutrition is higher than severe malnutrition. In addition, poor immunological response has been observed in moderate malnutrition [Cortés-Barberena et al, 2008].…”
Section: Discussionmentioning
confidence: 99%